F33 Task-switching abilities in pre-manifest huntington's disease subjects. (September 2018) - Migliore, Simone; D'Aurizio, Giulia; Maffi, Sabrina; Curcio, Giuseppe; Squitieri, Ferdinando
Abstract : Background: Huntington's Disease (HD) cognitive dysfunction may start before unequivocal motor signs become apparent. Main early cognitive abnormal domains may include deficits in psychomotor speed, negative emotion recognition and executive functioning. Previous studies have demonstrated an impaired performance in several frontal tasks in HD patients. Aim: The present study aimed to investigate the executive control of cognition in pre-manifest (pre) HD subjects, by means of a task-switching protocol. Methods: We enrolled 30 preHD subjects (DCL<4) that were subsequently assigned to two experimental groups: 15 to the preHD1 group (with a Total Motor Score-TMS ≤ 4) and 15 to the preHD2 group (with a 5 ≤TMS≤ 9). Their performance was compared with a group of 18 healthy controls (HC). Two different tasks were performed in rapid and random succession, so that the task was either changed from one trial to the next one (switch trials) or repeated (repetition trials). Switch trials are usually slower than repetitions, causing a so-called switch cost (SC). Results: preHD subjects showed slower reaction times than HC in both switch (pre-HD2: 1201.133±19.99; pre-HD 1: 1099.7±15.76; HC: 755.61±12.63; p<0.0001) and repetition trials (pre-HD2: 920.8±14.90; pre-HD1: 895.5±14.13; HC: 683.97±10.74; p=0.001), as also confirmed by a significantly increased SC (pre-HD2: 360.98±7.98; pre-HD1: 192.84±10.32; HC: 76.56±7.98; p=0.01). More specifically, preHD2 subjects showed a significantly impaired switching ability characterized by slower reaction times compared with both preHD1 and HC. Conclusions: The executive control is impaired before HD becomes manifest. Such abnormalities worsen in preHD subjects with first subtle motor features that are still insufficient and unspecific to document the onset. Considering that such abilities have obvious implication with behavior and independence, the beneficial effect of early rehabilitation programs focused on executive function should be tested.